The European Marine Observation and Data Network (EMODnet): Visions and Roles of the Gateway to Marine Data in Europe - Martín Míguez, Belén; Novellino, Antonio; Vinci, Matteo; Claus, Simon; Calewaert, Jan-Bart; Vallius, Henry; Schmitt, Thierry; Pititto, Alessandro; Giorgetti, Alessandra; Askew, Natalie; Iona, Sissy; Schaap, Dick; et al. (Frontiers in Marine Science, 2019)
Marine data are needed for many purposes: for acquiring a better scientific understanding of the marine environment, but also, increasingly, as marine knowledge for decision making as well as developing products and services supporting economic growth. Data must be of sufficient quality to meet the specific users’ needs. It must also be accessible in a timely manner. And yet, despite being critical, this timely access to known-quality data proves challenging. Europe’s marine data have traditionally been collected by a myriad of entities with the result that much of our data are scattered throughout unconnected databases and repositories. Even when data are available, they are often not compatible, making the sharing of the information and data aggregation particularly challenging. In this paper, we present how the European Marine Observation and Data network (EMODnet) has developed over the last decade to tackle these issues. Today, EMODnet is comprised of more than 150 organisations which gather marine data, metadata and data products and make them more easily accessible for a wider range of users. EMODnet currently consists of seven sub-portals: bathymetry, geology, physics, chemistry, biology, seabed habitats and human activities. In addition, Sea-basin Checkpoints have been established to assess the observation capacity in the North Sea, Mediterranean, Atlantic, Baltic, Artic and Black Sea. The Checkpoints identify whether the observation infrastructure in Europe meets the needs of users by undertaking a number of challenges. To complement this, a Data Ingestion Service has been set up to tackle the problem of the wealth of marine data that remain unavailable, by reaching out to data holders, explaining the benefits of sharing their data and offering a support service to assist them in releasing their data and making them available through EMODnet. The EMODnet Central Portal (www.emodnet.eu) provides a single point of access to these services, which are free to access and use. The strategic vision of EMODnet in the next decade is also presented, together with key focal areas towards a more user-oriented service, including EMODnet for business, internationalization for global users and stakeholder engagement to connect the diverse communities across the marine knowledge value chain.